2009
DOI: 10.1021/ol902320w
|View full text |Cite
|
Sign up to set email alerts
|

First Total Synthesis of Tubulysin B

Abstract: The first total synthesis of tubulysin B is described. The aziridine route to tubuphenylalanine (Tup) of the tubulysin D/U-series could not be transferred to the synthesis of tubutyrosine (blue moiety). Therefore, tubutyrosine (Tut) was synthesized by a Wittig olefination/diastereoselective catalytic reduction sequence. Interestingly, the C-2 epimer of tubulysin B has a cytotoxic activity almost identical to the natural diastereomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…All the synthetic procedures, compound characterizations and copies of 1 H, 13 C, 19 FNMR spectra and MS analyses are included in the Supporting Information.…”
Section: Experimental Section Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…All the synthetic procedures, compound characterizations and copies of 1 H, 13 C, 19 FNMR spectra and MS analyses are included in the Supporting Information.…”
Section: Experimental Section Chemistrymentioning
confidence: 99%
“…Synthetic strategiesb ased on the coupling of the four amino acids evidenced the criticali ssue of introducing the tertiary amide-N,O-acetal on the Tuvr esidue, along with its acid and base lability. Although solutions have been proposed in this sense, [11][12][13] to our knowledge none of the published syntheses have been used to secure sufficient amountso ft ubulysins for clinicald evelopment. Alternative strategies have been focused on the production of simplified analogues by replacement of the N,O-acetal moiety with hydrogen (tubulysins Ua nd Va nd their analogues) [7,[14][15][16][17] or alkyl and ÀCH 2 ÀOÀalkyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, tubulysins are only obtained in limited amounts as fermentation, isolation procedures as well as intricate chemical synthesis are quite challenging. 14, 15, 16 Pretubulysin, a natural precursor of tubulysins, although also of minute quantity in myxobacteria, was successfully synthesized in a large-scale setup 17 and firstly tested for its bioactivity and target in some tumor cell lines. 18, 19, 20 …”
mentioning
confidence: 99%
“…In 2006, the Ellman group reported the first synthesis of tubulysin D, [13] and recently Wessjohann et al described the first synthesis of tubulysin B. [14] In addition, the groups of Höfle [15] and Dömling [16] patented syntheses of tubulysins. Very recently, Tamura et al reported the conversion of tubulysin D into a cyclic derivative, bridging the N terminus of Tuv with an OH group α to the thiazole ring.…”
Section: Introductionmentioning
confidence: 99%